VD_FINDINFO Jug / 2013 / 107 vom 21. November 2012 - VD Tribunal cantonal (2012)
ACQUITTEMENT, HOMICIDE PAR NÉGLIGENCE, ACCIDENT DE LA CIRCULATION, CIRCULATION EN FILE, CIRCULATION ROUTIÈRETRAFIC ROUTIER, INDEMNITÉEN GÉNÉRAL | 117 CP, 12 al. 3 CP, 26 al. 1 LCR, 32 al. 1 LCR, 34 al. 3 LCR, 35 al. 3 LCR, 35 al. 5 LCR, 35 al. 6 LCR, 36 al. 1 LCR, 36 al. 3 LCR, 39 al. 2 LCR, 429 CPP (CH)